Doppler radar physiological sensing - Boric-Lubecke, Olga, 1966-; Lubecke, Victor M.; Droitcour, Amy D.; Park, Byung-Kwon; Singh, Aditya, 1984- (John Wiley & Sons, Inc., 2016)
Presents a comprehensive description of the theory and practical implementation of Doppler radar-based physiological monitoring This book includes an overview of current physiological monitoring techniques and explains the fundamental technology used in remote non-contact monitoring methods. Basic radio wave propagation and radar principles are introduced along with the fundamentals of physiological motion and measurement. Specific design and implementation considerations for physiological monitoring radar systems are then discussed in detail. The authors address current research and commercial development of Doppler radar based physiological monitoring for healthcare and other applications. . Explains pros and cons of different Doppler radar architectures, including CW, FMCW, and pulsed Doppler radar. Discusses nonlinear demodulation methods, explaining dc offset, dc information, center tracking, and demodulation enabled by dc cancellation. Reviews advanced system architectures that address issues of dc offset, spectrum folding, motion interference, and range resolution. Covers Doppler radar physiological measurements demonstrated to date, from basic cardiopulmonary rate extractions to more involved volume assessments Doppler Radar Physiological Sensing serves as a fundamental reference for radar, biomedical, and microwave engineers as well as healthcare professionals interested in remote physiological monitoring methods.